2013
DOI: 10.1080/14634988.2013.823075
|View full text |Cite
|
Sign up to set email alerts
|

Fishing for Dagaa with 5 mm and 10 mm mesh nets: A comparison of length-frequencies and biological characteristics

Abstract: Two mesh sizes (5 and 10 mm) usually used to harvest Rastrineobola argentea in Lake Victoria were assessed from April to September 2001 to determine their suitability. It was observed that 13.2% of fish caught in 5 mm and 11.2% caught in 10 mm for April, May, June and July were of a size below maturity (44 mm standard length, [SL]). Mean size of fish caught with the 5 mm mesh was 46.8 ± 1.2 mm and that of fish caught with the 10 mm mesh was 46.8 ± 0.5 mm (SL). Catches per unit effort (CPUE) from the two meshes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Paperna (1996), Van Dobben (1952 and Okedi (1981) reported that the tapeworm hamper the gonadal development and retarding maturation of the ovary of the host fish. Recently it has been reported by Nsinda et al (2013) that the tapeworm reduces fecundity of Dagaa fish Rastrineobola argentea in Lake Victoria.…”
Section: Averagementioning
confidence: 98%
“…Paperna (1996), Van Dobben (1952 and Okedi (1981) reported that the tapeworm hamper the gonadal development and retarding maturation of the ovary of the host fish. Recently it has been reported by Nsinda et al (2013) that the tapeworm reduces fecundity of Dagaa fish Rastrineobola argentea in Lake Victoria.…”
Section: Averagementioning
confidence: 98%
“…Both Dagaa and the Haplochromines have enormous potential for small-scale trading in local and regional marketplaces, acting as an affordable source of protein for both human and animal sustenance [3]. In addition, a sizable amount is transported to poultry factories to prepare animal feed [12].…”
Section: Oceanography and Fisheries Open Access Journalmentioning
confidence: 99%
“…The use of fabric materials as fishing nets was used at the beginning of the Dagaa (Rastrineobola argentea) fishery in Lake Victoria, followed by the introduction of lantern lamps (Karabai) [1][2][3]. The fishery is currently one of Lake Victoria's four commercial fisheries, the others being those for haplochromines, Nile perch (Lates niloticus), and Nile tilapia (Oreochromis niloticus) [4,5].…”
Section: Introductionmentioning
confidence: 99%